2020
DOI: 10.33258/biohs.v2i1.162
|View full text |Cite
|
Sign up to set email alerts
|

The Duties and Functions Performance of Aceh Human Resources Improvement Institutions in Scholarship Study Program Implementation in Aceh Government

Abstract: The ability of employees in carrying out the duties and functions of LPSDM can be manifested if the employee has good work motivation, both physiologically, safety, appreciation, social, and self-actualization. the fact shows that LPSDM Aceh has not been able to carry out its duties and functions properly. On the other hand, LPSDM Aceh has not been able to transparently select scholarship recipients. This happens because there are still many recipients of entrusted scholarships from the Aceh government, so tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…eory comes from practice, and it should return to practice to be tested by practice. In order to discuss and test the conclusions of this study in a wider range, based on the attitude of "throwing bricks to attract jade," according to the conclusions of the study and combined with the problems of some enterprises in the survey, some management countermeasures are put forward [23]. In the process of interview research, case study, and questionnaire, the author found that the human resources strategy of some enterprises is not very perfect.…”
Section: Discussionmentioning
confidence: 99%
“…eory comes from practice, and it should return to practice to be tested by practice. In order to discuss and test the conclusions of this study in a wider range, based on the attitude of "throwing bricks to attract jade," according to the conclusions of the study and combined with the problems of some enterprises in the survey, some management countermeasures are put forward [23]. In the process of interview research, case study, and questionnaire, the author found that the human resources strategy of some enterprises is not very perfect.…”
Section: Discussionmentioning
confidence: 99%
“…The results of the work can involve quality, quantity, and timeliness, but performance evaluation in a company's organization is key in employee development. Performance evaluation is in principle a manifestation of an employee's performance appraisal form (Irfansyah, 2020).…”
Section: Performancementioning
confidence: 99%
“…Performance is a goal-oriented process designed to ensure that organizational processes exist to maximize the productivity of employees, teams and ultimately the organization (Asbari et al, 2020). Employee performance is related to the work of company employees, work results are related to quality, quantity and timeliness, and company performance evaluation is the key to success (Irfansyah, 2020). Zafar et al (2017) stated that employee performance is one of the keys to the success of an organization, therefore management usually looks for ways to increase the level of employee performance through various means according to the organization's mission, so that people use resources to complete tasks effectively and efficiently (Bedarkar & Pandita, 2014;Van Dolen et al, 2004).…”
Section: Introductionmentioning
confidence: 99%